Hydrocephalus Following Giant Transosseous Vertex Meningioma Resection - Schmidt, Bradley T.; Cikla, Ulas; Kozan, Abdulbaki; Dempsey, Robert J.; Baskaya, Mustafa K. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction Meningiomas are among the most common primary intracranial tumors. While well-described, there is limited information on the outcomes and consequences following treatment of giant-sized vertex-based meningiomas. These meningiomas have specific risks and potential complications due to their size, location, and involvement with extracalvarial soft tissue and dural sinuses. Herein, we present four giant-sized vertex transosseous meningioma cases with involvement and occlusion of the sagittal sinus, that postoperatively developed external hydrocephalus and ultimately required shunting.Methods A retrospective chart review identified patients with large vertex meningiomas that were: (1) large (>6 cm) with hemispheric (no skull base) location, (2) involvement of the superior sagittal sinus resulting in complete sinus occlusion, (3) involvement of dura resulting in a large duraplasty area, (4) transosseous involvement requiring a 5 cm or larger craniectomy for resection of invaded calvarial bone.Results Tumors were resected in all four cases, with all patients subsequently developing external hydrocephalus which required shunting within 2 weeks to 6 months postsurgery.Conclusion We believe this may be the first report of the development of hydrocephalus following surgical resection of these large lesions. Based on our observations, we propose that a combination of superior sagittal sinus occlusion and changes in brain elasticity and compliance affect the brain's CSF absorptive capacity, which ultimately lead to hydrocephalus development. We suggest that neurosurgeons be aware that postoperative hydrocephalus can quickly develop following treatment of giant-sized vertex-based meningiomas, and that correction of hydrocephalus with shunting can readily be achieved.
Keywords: transosseous meningiomas; hydrocephalus; shunt; vertex; meningioma; postoperative hydrocephalus; tumor resection